DAMPAK BANJIR TERHADAP INFRASTRUKTUR DI KABUPATEN WAJO BERBASIS DATA CITRA MODIS NRT - Rauf, Syafruddin; Aboe, A. Faisal; Wahyuni, Herna (Jurnal Transportasi, 2017)
Abstract Flood response using earth satellite imagery in the form of Near Real Time is needed today, at national, regional, and local levels, due to high flood risk in Indonesia. The fundamental thing in flood disaster management in Indonesia is the absence of accurate data about the condition of flood events, at the time of the occurrence or after the flood disaster. This study aims to apply image data processing MODIS Near Real Time and mapping to be used in mitigation post flood disaster process. Road and building infrastructure data is obtained from the Open Street Map. Open Street Map data and Near Real Time MODIS image data were processed with QGIS Open Source program to analyze the impact of flood on road and building infrastructure in Wajo Regency. The results of the analysis explain that there are 10 districts affected by floods in Wajo Regency, with the biggest flood affected areas are Kecamatan Pammana, Kecamatan Belawa District, Kecamatan Sabbangparu, and Kecamatan Bola. Keywords: flood disaster, flood risk, earth satellite imagery, image data  Abstrak Respon banjir menggunakan citra satelit bumi dalam bentuk Near Real Time sangat dibutuhkan saat ini, baik di tingkat nasional, tingkat regional, maupun tingkat lokal, karena risiko banjir yang yang tinggi di Indonesia. Hal yang mendasar dalam penanggulangan bencana banjir di Indonesia adalah belum adanya data yang akurat tentang kondisi kejadian banjir, pada saat terjadinya maupun pascabencana banjir. Studi ini bertujuan untuk mengaplikasikan pengolahan data citra MODIS Near Real Time dan melakukan pemetaan untuk dapat digunakan dalam proses penanggulangan pascabencana banjir. Data infrastruktur jalan dan bangunan diperoleh dari Open Street Map. Data Open Street Map dan data citra MODIS Near Real Time diolah dengan program QGIS Open Source untuk menganalisis dampak banjir tehadap infrastruktur jalan dan bangunan di Kabupaten Wajo. Hasil analisis menjelaskan bahwa terdapat 10 kecamatan yang terdampak banjir di Kabupaten Wajo, dengan wilayah yang terdampak banjir terbesar adalah Kecamatan Pammana, Kecamatan Belawa, Kecamatan Sabbangparu, dan Kecamatan Bola. Kata-kata kunci: bencana banjir, risiko banjir, citra satelite bumi, data citra